PENGARUH LATIHAN IMAGERY TERHADAP KECEPATAN REAKSI PADA ATLIT PENCAK SILAT PERISAI DIRI PEKANBARU - Anggraini, Putri; Ramadi, Ramadi; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The purpose of this research is to find out if there is The Effect Of Exercise Imagery to The Speed Of Reaction team Pencak Silat Perisai Diri Pekanbaru So, the design of this study uses a group of the researce is wearing one group pretest posttest design. With the team pencak silat persai diri Pekanbaru pamounting to 4 people. The sample in this study uses technique of sampling of saturated sample where all population sampled.. The instruments used in this study is a tast to kikc the ball with the foot of the insid,the aim is to gauge the skills of passing footbal. After that, the data processed by the statistic to test normality with a lilifors test the first significant Î± (0.05). The hypothesis put forward is the the influence of the pass and support to the skils of passing. Based on the analysis of statistical data, the data pree test Lcount of 0,209, data post test Lcount of 0,216 and Ltabel 0,216, then Lcount < Ltabel. then the data is normal with an increase of 0.07. Based on T test analysis produces Tcount> Ttabel of 3,5 and 2,353, meaning Tcount> Ttabel. Thus, there is The Effect of Exercise Imagery to The Speed of Reaction Team Pencak Silat Perisai Diri Pekanbaru.Keywords : Imagery, Speed Reaction